Updates on Cancer Treatment 2015
DOI: 10.5772/60548
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Pain — The Role of an Integrated, Comprehensive Rehabilitation Program in Its Management

Abstract: there appears to be a deficiency in the training of physicians and nurses. Both physicians and nurses indicated that "inability to properly assess the pain" and "inadequate knowledge about pain management" ranked among the most relevant barriers preventing a multidisciplinary approach to pain treatment and adequate cancer pain management. [8] Despite the increasing availability of pain medications, pain continues to be deemed as moderate-to-severe in more than 50% of cancer patients. According to a recent popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…Patients were more cooperative in postoperative chemotherapy and their overall recovery when they were in a healthy psychological and physiological state. Our results are consistent with a literature report, in which Saggini et al concluded that comprehensive rehabilitation therapy in cancer patients significantly improves patients' quality of life ( 21 ). In the present study, we did not however develop different comprehensive rehabilitation treatment plans for patients at different stages of cholangiocarcinoma, which is the limitation of the current research, and still needs to be addressed.…”
Section: Discussionsupporting
confidence: 93%
“…Patients were more cooperative in postoperative chemotherapy and their overall recovery when they were in a healthy psychological and physiological state. Our results are consistent with a literature report, in which Saggini et al concluded that comprehensive rehabilitation therapy in cancer patients significantly improves patients' quality of life ( 21 ). In the present study, we did not however develop different comprehensive rehabilitation treatment plans for patients at different stages of cholangiocarcinoma, which is the limitation of the current research, and still needs to be addressed.…”
Section: Discussionsupporting
confidence: 93%
“…This includes functional and musculoskeletal issues such as loss of muscular and cardiac fitness, fatigue, impaired motor sensory function and lymphoedema [ 6 ]. Cancer multidisciplinary rehabilitation is found by the literature [ 7 – 9 ] to minimize these effects in its capacity as a key element of the care that cancer patients receive, aiming to minimize long-term complications, reducing hospital re-admissions and improving quality of life [ 7 – 9 ]. Cancer rehabilitation assists individuals to achieve the best possible physical, psychological, social and vocational outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the now well-known beneficial effects on bone, the vitamin D has positive extraskeletal effects; it acts on the muscle directly (receptor have been identified in skeletal muscle) and indirectly, through increasing of calcium that is essential for muscle contraction; and finally, it promotes the synthesis of contractile proteins [94]. Even supplements, such as omega-3 and carnitine, are widely recommended in this area [96,97].…”
Section: Nutritional-supplementary-integrative-interventionmentioning
confidence: 99%